2020
DOI: 10.5027/andgeov47n2-3188
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry and spatial distribution of glacial cirques in the Western Fuegian Andes of Argentina, southernmost South America

Abstract: Glacial cirques comprise a distinctive element of relief in alpine landscapes, and their morphometry, distribution and spatial arrangement are generally linked to morphoclimatic factors. This study provides an analysis of morphometric characteristics, floor altitude, aspect and distribution of 251 first-order and 99 "inner" cirques with regard to environmental agents in a selected alpine-type area of the southwestern Fuegian Andes, in Southern Argentina. Parametric variables were extracted and quantified from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 109 publications
(212 reference statements)
0
1
0
Order By: Relevance
“…Cirques are present almost ubiquitously in formerly glaciated regions. They have been studied throughout the world [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], and these studies have shown that cirque morphology is linked to the paleoclimate. For example, a large cirque size indicates that former glaciers were dynamic or long-lasting; the cirque floor altitude (CFA) is an indicator of the former glacial equilibrium line altitude (ELA) and reflects information about the former moisture and wind directions; and the cirque aspect indicates information about the solar radiation, wind direction, and glacial extensions [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cirques are present almost ubiquitously in formerly glaciated regions. They have been studied throughout the world [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], and these studies have shown that cirque morphology is linked to the paleoclimate. For example, a large cirque size indicates that former glaciers were dynamic or long-lasting; the cirque floor altitude (CFA) is an indicator of the former glacial equilibrium line altitude (ELA) and reflects information about the former moisture and wind directions; and the cirque aspect indicates information about the solar radiation, wind direction, and glacial extensions [ 2 ].…”
Section: Introductionmentioning
confidence: 99%